Knowledge, attitudes and practices of the population regarding osteoporosis (One Health & Risk Management, 2023)
Introduction. Introduction. Osteoporosis is a skeletal disease characterized by compromising the mechanical strength of the bone and increasing the risk of fractures. Osteoporosis conditions the increase in illness and disability in the elderly and, respectively, leads to an increase in health expenses.Material and methods. A cross-sectional descriptive epidemiological study was designed, which included surveying 423 respondents and interviewing representatives of health decision-makers (6 in-depth interviews), during 2020-2022. Results. In the section on knowledge about osteoporosis, a dissociation of responses was recorded according to the gender criterion – women in 65.4% of cases know better about this problem (χ2=3.898, p=0.273). Knowledge about the fact that osteoporosis can occur during menopause was demonstrated by 45.9% of respondents, of whom women in 76.3% of cases (χ2=36,136,183, p
Keywords: osteoporosis; knowledge; attitudes; practices; risk factors; health decision factors; prevention